Minimally Invasive Approach for the Treatment of Pancreatic Pseudcyst. Transgastric Drainage - Where We Are Now? - Perišić, Nenad; Bezmarević, Mihailo; Doder, Radoje; Brčerević, Irina; Petrović, Stanko (Vojnosanitetski pregled, 2021)
Introduction: Minimally invasive approach for the treatment of acute pancreatitis (AP) and its complications has proven to reduce morbidity and mortality rate, length of hospitalization and costs of treatment, and improve quality of life of the patients. This approach for the AP has been implemented in developed countries, but in our region lags behind. In this case report we present the successful endoscopic transgatsric drainage of the large pancreatic pseudocyst (PPC) developed as a complication of AP.Case Report: A 63 years old male patient was presented with nausea and vomiting as a consequence of the compressive effects of PPC in the body and tail of the pancreas after episode of AP. On computed tomography (CT) scan it was shown a cystic formation in the region of the pancreatic body and tail compressing stomach which was verified on upper endoscopy. Under fluoroscopy using lateral duodenoscope the biliary plastic prostheses of 12 French and 8 cm of length was placed throughout posterior stomach wall into PPC. The intervention was finished uneventful without complications. On CT scan performed 7 days after procedure the reduction of the PPC size was significant and control CT scan one month after the procedure and removal of the prosthesis showed almost complete resolution of the PPC.Conclusion: Endoscopic transgastric drainage is safe and effective procedure for PPCs especially when PPC has propulsion effects on stomach wall.